The Effect of Synergetic Teaching Method Application on Learning Outcomes of The Circulatory System Topic Public Senior High School 11 in Banda Aceh (Online Based Learning) - Suci Amalia; Hasanuddin Hasanuddin; Khairil Khairil; Supriatno Supriatno; Dewi Andayani (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2021)
ABSTRACT It aims to recognize the influence of implementing synergetic teaching procedures on student learning outcomes in the circulation system module. The research was conducted in October 2020 using the True Experimental Design procedure with the pre-test post-test countroul group design. Parameters The parameters used are the learning outcomes that are measured via the pre-test and post-test. The information obtained was then tabulated and analyzed using the t test against the comparison of the mean value of N-Gain in the experimental class and the control class. The results of the information analysis obtained t hit = 2.11 t table = 1.67. The conclusion of this research shows that the application of synergetic teaching procedures affects student learning outcomes in the circulation system module.Keywords: synergetic teaching, learning outcomes, applicationPENGARUH PENERAPAN METODE SYNERGETIC TEACHING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI SISTEM SIRKULASI DI SMA NEGERI 11 BANDA ACEH (PEMBELAJARAN BERBASIS DARING) Suci Amalia(1), Hasanuddin (1), Khairil (1), Supriatno(1), Dewi Andayani(1)1Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Syiah Kuala, Banda Aceh*Email: Suciamalia026@gmail.com ABSTRAKBertjuan untuk mengenali terdapatnya pengaruh pelaksanaan tata cara synergetic teaching terhadap hasil belajar peserta didik pada modul sistem sirkulasi. Penelitian dilakukan bulan Oktober Tahun 2020 dengan tata cara True Experimental Design dengan desain pre-test post-test countroul group. Parameter Parameter yang digunakan ialah merupakan hasil belajar yang diukur lewat pre-test dan post-test. Informasi yang diperoleh berikutnya ditabulasi serta dianalisis memakai uji t terhadap perbandingan nilai rata-rata N-Gain pada kelas eksperimen serta kelas kontrol. Hasil analisis informasi diperoleh t hit = 2,11 t tabel = 1,67. Simpulan dari penelitian ini menampilkan kalau penerapan tata cara synergetic teaching pengaruhi hasil belajar peserta didik pada modul sistem sirkulasi.Kata Kunci: synergetic teaching, hasil belajar, penerapan